Evaluating Research Trends and Scholarly Impact in Blended Learning and Learning Management Systems: A Bibliometric Study (2003–2025) - Ishaq Ishaq; Syamsidar Saleng; Hartono Bancong (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify global research trends, thematic evolution, and collaboration patterns in blended learning and learning management systems (LMS) from 2003 to 2025 using a bibliometric approach. Methodology:.A total of 890 peer-reviewed documents indexed in Scopus were analyzed using VOSviewer (v1.6.19) and Biblioshiny (R-based). Bibliometric mapping, keyword co-occurrence, and network visualization techniques were employed following systematic review procedures. Main Findings: The study identified three distinct research phases: initiation (2003–2008), rapid growth (2009–2019), and stabilization (2020–2025). Research focus shifted from technical implementation to learner-centered pedagogy emphasizing engagement, curriculum integration, and learning analytics. Emerging themes include artificial intelligence and adult learning, while Computers & Education remains the most influential source. Novelty/Originality of this study: This study provides a two-decade bibliometric mapping highlighting thematic evolution and collaboration networks in blended learning and LMS research. It advances understanding by identifying emerging areas such as AI and lifelong learning that inform future directions in digital education research.